2024
DOI: 10.18632/aging.205635
|View full text |Cite
|
Sign up to set email alerts
|

Chlorogenic acid prevents ovariectomized-induced bone loss by facilitating osteoblast functions and suppressing osteoclast formation

Chien-Yi Ho,
Chih-Hsin Tang,
Trung-Loc Ho
et al.

Abstract: Osteoporosis is a usual bone disease in aging populations, principally in postmenopausal women. Anti-resorptive and anabolic drugs have been applied to prevent and cure osteoporosis and are associated to a different of adverse effects. Du-Zhong is usually applied in Traditional Chinese Medicine to strengthen bone, regulate bone metabolism, and treat osteoporosis. Chlorogenic acid is a major polyphenol in Du-Zhong. In the current study, chlorogenic acid was found to enhance osteoblast proliferation and differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…In recent years, CGA has been reported to reduce osteoclast differentiation and bone resorption. It was also shown to increase tibial mineralization and improve bone strength of the femoral backbone in in vivo experiments, which may be related to its regulation of the RANKL signaling pathway (Kuroyanagi et al, 2017;Chen et al, 2021;Ho et al, 2024). RANKL can bind to the RANK receptor on the surface of osteoblasts, thereby activating a number of major intracellular signaling pathways, including nuclear factor-κB (NF-κB), JNK, ERK, and p38 MAPK.…”
Section: Cga Regulated the Rankl Signaling Pathwaymentioning
confidence: 99%
“…In recent years, CGA has been reported to reduce osteoclast differentiation and bone resorption. It was also shown to increase tibial mineralization and improve bone strength of the femoral backbone in in vivo experiments, which may be related to its regulation of the RANKL signaling pathway (Kuroyanagi et al, 2017;Chen et al, 2021;Ho et al, 2024). RANKL can bind to the RANK receptor on the surface of osteoblasts, thereby activating a number of major intracellular signaling pathways, including nuclear factor-κB (NF-κB), JNK, ERK, and p38 MAPK.…”
Section: Cga Regulated the Rankl Signaling Pathwaymentioning
confidence: 99%
“…CLJC is an experienced formula by professor Zhang wentai of the department of orthopedics of the affiliated hospital of changchun university of traditional chinese medicine, which is a traditional chinese medicine preparation developed on the basis of the theory of traditional chinese medicine and is also a drug recommended by China Food and Drug Administration (CFDA) for the treatment of osteoporosis ( 22 ).As a prescription for bushen zhuanggu, CLJC consists of Eucommia ulmoides, Angelica sinensis, Panaxnotoginseng, Amomum villosum Lour, Zhishouwu, Leech, Cartialgenous, Chinemys reevesii, and Dried human placenta , which can significantly increase cortical bone thickness and trabecular bone width, improving osteoblast activity and promoting bone formation in ovariectomized (OVX) rats ( 23 ). At the same time, clinical studies showed that CLJC combined with other drugs can also increase the bone density and improve the bone metabolic index, which enhances the quality of life of patients ( 24 ).…”
Section: Introductionmentioning
confidence: 99%